ANALISIS LEGALISASI GANJA MEDIS UNTUK PEMENUHANHAKATAS KESEHATAN WARGA NEGARA - Nugroho, Achmad Arryo; Husodo, Jadmiko Anom; Hermawan, Sapto (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2025)
This study aims to understand the use of medical cannabis for fulfilling citizens' health rights based on scientific research. The study examines the potential positive impacts of legalizing medical cannabis and the potential risks that might occur when a country legalizes medical cannabis. Additionally, it analyzes whether Indonesia should legalize medical cannabis based on existing scientific research. This study employs normative legal research and has a prescriptive- analytical nature, using statutory approaches, historical approaches, case approaches, comparative approaches, and conceptual approaches. This study uses primary legal materials, which are legal materials issued by official government institutions, and secondary legal materials, consisting of document publications not officially issued by state agencies. The results of the study indicate that scientific research on the potential benefits of legalizing medical cannabis is still limited. The lack of comprehensive research means that medical cannabis is not yet fully understood, and many potential benefits and risks still need to be validated. Moreover, in the context of medical cannabis, the supervision of drug distribution plays a crucial role in preventing the misuse of medical cannabis itself.Considering the known potential benefits and risks, Indonesia should not rush to legalize the use of cannabis for medical purposes. Just because many countries have started to legalize the use of cannabis for medical purposes does not mean Indonesia should force itself to legalize medical cannabis, especially since the scientific research is still in its early stages and requires further investigation